Could We Talk about Environmental Protection in Mediaeval Serbia? - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The „Saxons“ (in Serbian Sasi), i.e. German immigrants, who were engaged in mining and metallurgy, had cleared forests and squatted in the same way as the original Serbs; Emperor (Tsar) Dushan (Dušan) was determined to stop this. From henceforth (i.e. State Council from the year 1349, which promulgated the first part of the Law Code), the Saxons may not clear and that forest which they clear shall not belong to them, nor shall they settle people there, but it shall stand empty, so that the forest grow. Emperor has allowed to Saxons such timber as they needed for fuel or constructional work.  And if they have unlawfully taken any land from any lord (vlastelin), let the lord sue them according to the law of the Sainted King (i.e. King Milutin, Dushan’ grandfather).